An empirical model of growth through product innovation - Rasmus Lentz; Dale T. Mortensen (Institute for the Study of Labor (IZA), 2005)
Productivity dispersion across firms is large and persistent, and worker reallocation among firms is an important source of productivity growth. The purpose of the paper is to estimate the structure of an equilibrium model of growth through innovation that explains these facts. The model is a modified version of the Schumpeterian theory of firm evolution and growth developed by Klette and Kortum (2004). The data set is a panel of Danish firms than includes information on value added, employment, and wages. The model's fit is good and the structural parameter estimates have interesting implications for the aggregate growth rate and the contribution of worker reallocation to it.
Keywords: E22; E24; J23; J24; L11; L25; O3; O4; 330; labor productivity growth; worker reallocation; firm dynamics; firm panel data estimation; Wachstumstheorie; Innovation; Arbeitsproduktivität; Schätzung; Dänemark